Integrative counselling and psychotherapy : a textbook - Spalek, Basia; Spalek, Mark (Routledge, 2019)
Integrative Counselling and Psychotherapy: A Textbook is an engaging and comprehensive guide to integrative counselling, providing an explanation of the theoretical ideas underpinning person-centred, interpersonal, cognitive-behavioural (CBT) and hypnotherapeutic modalities. Divided in two major sections, this book first provides a detailed exploration of the key integrative concepts - presence, emotional and psychological processing, attachment, thinking, and the unconscious - and then practically applies these concepts to the issues commonly brought by clients to therapy. With the help of case studies, exercises and chapter questions, Integrative Counselling and Psychotherapy will be essential reading for students on integrative counselling and psychotherapy courses and for integrative practitioners.